Non-Darcy Porous Medium of Brownian Motion and Thermophoresis on Mixed Convection Nanofluid Flow Past a Wedge with Double Dispersion - Padma, S.V.; Mallesh, M.P.; Munjam, Shankar Rao; Nisar, Kottakkaran Sooppy (Journal of Applied Nonlinear Dynamics, 2026)
The aim of this numerical simulation is to investigate the heat and mass transfer on mixed convection nanofluid flow over a vertical wedge with double dispersion, thermophoresis and Brownian motion. Non-similarity transformations are used to transform the continuum equations which govern the flow in to dimensionless form and the obtained ordinary differential equations are evaluated using Shooting with Runge Kutta 4th order. The emerging parameters such as D_f and D_s - Solutal and thermal, N_r -Buoyancy ratio, N_t -Thermophoresis, N_b -Brownian motion, and m -wedge angle impacts on coefficients of heat and mass transfer, Concentration, Temperature, and Velocity are demonstrated through tables and graphs. The coefficient of heat and mass transfer amplifies with amplification in m. The outcome of the current investigation is accurate when compared with existing work. The present article is suitable to the solutal and thermal flow of nanomaterials processing in environmental engineer-ing, the chemical industry, and food technology.